1999
DOI: 10.1111/j.1745-4603.1999.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Model Acid Milk Beverage: Effect of Pectin Concentration, Storage Temperature and Milk Heat Treatment

Abstract: Acid milk beverages were made by homogenizing and diluting acid milk gels made with glucono-b-lactone. A central composite experimental design and response suqace methodology were used. Colloidal stability was assessed by the amount of surface whey produced during storage, the flow behaviour and particle size distribution. Using regression analysis a second order polynomial model satisfactorily predicted the @ect of pectin concentration on whey separation (R' = 0.88). Whey separation was significantly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 11 publications
6
42
0
13
Order By: Relevance
“…These observations were confirmed by turbidity measurement of the whey layer which was much higher for AMDs prepared with either pectins than for the control sample, and the turbidity was increased by the increase of pectin concentration. In literature, the turbidity of the whey layer was linked to its quantity, and higher turbidity corresponded to less whey separation (Lucey et al, 1999). The higher observed values for turbidity in case of AMDs with added pectin compared to control sample were probably related both to the soluble pectin present and remaining non sedimented proteins.…”
Section: Storage Stability Of Acidified Milk Drinksmentioning
confidence: 48%
See 1 more Smart Citation
“…These observations were confirmed by turbidity measurement of the whey layer which was much higher for AMDs prepared with either pectins than for the control sample, and the turbidity was increased by the increase of pectin concentration. In literature, the turbidity of the whey layer was linked to its quantity, and higher turbidity corresponded to less whey separation (Lucey et al, 1999). The higher observed values for turbidity in case of AMDs with added pectin compared to control sample were probably related both to the soluble pectin present and remaining non sedimented proteins.…”
Section: Storage Stability Of Acidified Milk Drinksmentioning
confidence: 48%
“…To assist the stabilization of casein particles by pectin (Lucey, Tamehana, Singh, & Munro, 1999), samples were homogenized using a high pressure homogenizer (Stansted Fluid Power, Pressure cell homogenizer, UK) at 20 MPa at 4 C. The samples were subsequently heated to 70 C in a shaking water bath, then re-homogenized at the same pressure, reheated to 70 C and incubated for 10 min. The AMD containing pectin were cooled down to room temperature and used for further analysis.…”
Section: Preparation Of Acidified Milk Drinkmentioning
confidence: 99%
“…While addition of pectin decreased wheying off at higher levels of 0.5 and 0.6% (Table 5). Lucey et al (1999) reported reduction in whey separation with the increase in the concentration of pectin in acid milk beverage.…”
Section: Optimization Of Independent Variablesmentioning
confidence: 99%
“…Torre et al (2003) reported that viscosity values of set-type fermented milks made with different commercial probiotics were between 15.8 and 23.3 mPa s. Fermented milk beverages were found to be non-Newtonian fluids with shear thinning (Butlert and McNulty 1995;Kristensen et al 1997;Lucey et al Penna et al 2001;Koksoy and Kilic 2003). Consistency index (K) and flow behavior index (n) and correlation coefficients of these constants were shown in Table 3.…”
Section: Rheological Characterizationmentioning
confidence: 99%